Control system of a high-power infrared free electron laser - Gorniker, E.I.; Gudkov, B.A.; Evtushenko, Yu.A.; Kondakov, A.A.; Kurkin, G.Ya.; Oreshkov, A.D.; Ovchar, B.K.; Salikova, T.V.; Scheglov, M.A.; Tararyshkin, S.V.; Tribendis, A.G.; Vinokurov, N.A. (Вопросы атомной науки и техники, 2001)
The control system of the high power infrared FEL is built on the base of a two-level distributed system. The system includes the operator interface at the upper level and Input/Output Controllers under supervision of the real time operating system at the lower level. All hardware for the control system of the FEL is produced by our institute, which solves several problems of hard real time and reduces cost of equipment.